2012
DOI: 10.1038/npp.2012.240
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Specific Modulation of Risk-Based Decision Making by Nucleus Accumbens Dopamine

Abstract: The nucleus accumbens (NAc) serves as an integral node within cortico-limbic circuitry that regulates various forms of cost-benefit decision making. The dopamine (DA) system has also been implicated in enabling organisms to overcome a variety of costs to obtain more valuable rewards. However, it remains unclear how DA activity within the NAc may regulate decision making involving reward uncertainty. This study investigated the contribution of different DA receptor subtypes in the NAc to risk-based decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
100
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 56 publications
14
100
3
Order By: Relevance
“…Therefore, we think it is justified to state that the deficits in reversal learning, probabilistic discounting and punished reward taking evoked by chemogenetic mesoaccumbens stimulation is the result of increased DA signaling in the NAc. Reversal learning impairments have previously been reported after systemic or intra-NAc treatment with a DA D2 receptor agonist in rats and humans [47][48][49] , whereas probabilistic discounting seems to be dependent on DA D1 rather than D2 receptor stimulation in the NAc 50 . Together, this suggests that the behavioral effects of mesoaccumbens hyperactivity observed here rely on stimulation of both DA receptor subtypes, depending on the task structure.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, we think it is justified to state that the deficits in reversal learning, probabilistic discounting and punished reward taking evoked by chemogenetic mesoaccumbens stimulation is the result of increased DA signaling in the NAc. Reversal learning impairments have previously been reported after systemic or intra-NAc treatment with a DA D2 receptor agonist in rats and humans [47][48][49] , whereas probabilistic discounting seems to be dependent on DA D1 rather than D2 receptor stimulation in the NAc 50 . Together, this suggests that the behavioral effects of mesoaccumbens hyperactivity observed here rely on stimulation of both DA receptor subtypes, depending on the task structure.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, a recent report showed that ventral striatal quinpirole administration had no effect on choice behavior in a probability-discounting task, which is similar to the RDT but in which the 'cost' associated with the large reward is risk of reward omission (Stopper et al, 2013). The authors attributed the lack of quinpirole effects to a greater role for D3 than D2 receptors in this task.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a risk discounting task that involved withinsession shifts of large reward probabilities, inactivation of the AcbS reduced the bias toward larger-magnitude rewards (Stopper & Floresco, 2011), suggesting that the AcbS may play a subtle and task-dependent role in risk-based decisionmaking. DA signals in the whole Acb support risk-based decision-making (Stopper, et al, 2013); however, the selective contribution of DA signals in the AcbS has not been investigated so far. Our data suggest that AcbS DA input may not play a major role to support the capacity to evaluate magnitude and likelihood of rewards associated with different levers, at least in a probabilistic choice task that involves probability discounting across sessions with fixed within-session reward probabilities.…”
Section: Acbs Dopamine and Probabilistic Choicementioning
confidence: 99%
“…Our data suggest that AcbS DA input may not play a major role to support the capacity to evaluate magnitude and likelihood of rewards associated with different levers, at least in a probabilistic choice task that involves probability discounting across sessions with fixed within-session reward probabilities. However, it is possible that AcbC DA depletion, similar to intra-Acb infusion of DA receptor antagonists (Stopper, et al, 2013), alters risky choice in tasks that involve within-session shifts of reward probabilities (Cardinal & Howes, 2005;St Onge & Floresco, 2009) demanding more complex cognitive processes, i.e., a persistent evaluation and updating of the current values associated with the available response options.…”
Section: Acbs Dopamine and Probabilistic Choicementioning
confidence: 99%
See 1 more Smart Citation